A composite strengthened glass based on pre-lithiation and two-step ion exchange and a preparation method thereof

CN122958073APending Publication Date: 2026-10-23IRICO +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610951778.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-29
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

但将锂交换作为独立的功能性预处理步骤,与传统二强工艺在时间和空间序列上进行创新性组合,以此构建独特且更优化的应力曲线结构的技术方案,目前尚未见公开报道

Benefits of technology

本发明提供了一种基于预锂化与二步离子交换的复合强化玻璃的制备方法,通过创新性地将锂交换的深层改性能力与钾/钠二强交换的高强度构筑能力在时间和空间维度有机结合,实现了1+1>2的协同强化效应,其中预锂化工艺形成了深层柔韧的改性基础,后续钾/钠二强交换工艺在此基础上构建了高强度的表层结构。该协同机制使玻璃获得独特的“高表面峰-平缓深基”复合应力结构,高表面压应力可显著提升玻璃的硬度与抗刮擦性能,极大的压应力层深度(DOL)和平滑的应力梯度则能有效抑制深层裂纹的萌生与扩展,大幅增强玻璃的抗冲击、抗跌落及抗疲劳性能。同时,深层基础压应力区能够有效锚定中心张应力,在实现高表面压应力与深压应力层的同时,将中心张应力(CT)控制在较低水平,显著降低玻璃因应力失衡引发的自爆风险,提升了产品的长期使用可靠性。此外,本发明三步法工艺的温度、时间、熔盐成分等关键参数可独立精确调控,能够针对不同玻璃组成和目标性能需求进行定制化应力曲线设计,具备极强的工艺灵活性与可操作性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958073A_ABST
    Figure CN122958073A_ABST
Patent Text Reader

Abstract

The application discloses a kind of composite strengthened glass based on prelithiation and two-step ion exchange and preparation method thereof, belong to the technical field of special glass chemical strengthening.The preparation method includes the following steps: lithium-sodium-aluminum-silicon glass or sodium-aluminum-silicon glass substrate is immersed in the first molten salt containing lithium ions to carry out first ion exchange (i.e.pre-lithiation treatment), and pre-lithiated glass is prepared;Pre-lithiated glass is immersed in the second molten salt containing sodium ions to carry out second ion exchange, and intermediate glass is prepared;The intermediate glass is immersed in the third molten salt containing potassium ions to carry out third ion exchange, and composite strengthened glass is prepared.The method is modified by first deep "pre-lithiation", then two-step ion exchange is refined, so as to build a composite compressive stress structure with "high surface stress peak" and "deep and thick flat stress base layer" in the glass, and the synchronous significant improvement of strength, toughness and reliability is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of chemical strengthening technology for special glass, specifically relating to a composite strengthened glass based on pre-lithiation and two-step ion exchange and its preparation method. Background Technology

[0002] Chemical strengthening (ion exchange) is a core technology for improving the mechanical properties of glass. Its principle involves transferring small-radius alkali metal ions (such as Na+) to the glass surface. + ) and ions with larger radii in molten salt (such as K+) + The process involves exchanging potassium ion exchange molecules to form a compressive stress layer (CS) on the glass surface, effectively improving the glass's bending strength and scratch resistance. Currently, the mainstream chemical strengthening technologies in the industry mainly include single-step potassium ion exchange and two-step ion exchange (two-strength) processes. The single-step potassium ion exchange process is simple and can achieve high surface compressive stress (CS), but it has inherent defects such as a shallow depth of compressive stress layer (DOL) and a steep stress gradient, resulting in limited impact resistance and crack propagation resistance of the glass, and a risk of spontaneous breakage due to excessively high central tensile stress (CT). The two-step ion exchange process is an improvement on the single-step method. Typically, the first step forms high surface compressive stress (CS) in low-temperature KNO3 molten salt, and the second step deepens the compressive stress layer depth (DOL) and smooths the stress gradient in high-temperature NaNO3 / KNO3 mixed molten salt. However, when pursuing ultimate mechanical properties, this process still faces an irreconcilable "inverse relationship" between surface compressive stress and compressive stress layer depth, and its ability to control the deep stress distribution of the glass is very limited.

[0003] Lithium ion (Li + Due to its smallest ionic radius and highest diffusion coefficient among alkali metals, lithium has been primarily used in chemical strengthening applications to reduce central tensile stress or to perform full lithium exchange. However, a technical solution that innovatively combines lithium exchange as an independent functional pretreatment step with traditional dual-strength processes in terms of time and spatial sequence to construct a unique and more optimized stress curve structure has not yet been publicly reported.

[0004] Therefore, there is an urgent need to develop a new composite chemical strengthening process that can synergistically improve the surface compressive stress and compressive stress layer depth of glass, while achieving a smoother and more reasonable internal stress distribution, thereby breaking through the performance bottleneck of existing technologies. Summary of the Invention

[0005] In order to overcome the shortcomings of the prior art, the present invention aims to provide a composite reinforced glass based on pre-lithiation and two-step ion exchange and its preparation method. The method first performs deep "pre-lithiation" modification and then performs refined two-step ion exchange, thereby constructing a composite compressive stress structure in the glass that combines "high surface stress peak" and "deep and gentle stress base layer", achieving a simultaneous and significant improvement in strength, toughness and reliability.

[0006] To achieve the above objectives, the present invention employs the following technical solution: This invention provides a method for preparing composite strengthened glass based on pre-lithiation and two-step ion exchange, comprising the following steps: Pre-lithiated glass is prepared by immersing a lithium sodium aluminum silicon glass substrate or a sodium aluminum silicon glass substrate in a first molten salt containing lithium ions for the first ion exchange (i.e., pre-lithiation treatment). Pre-lithiated glass is immersed in a second molten salt containing sodium ions for a second ion exchange to obtain intermediate glass; The intermediate glass is immersed in a third molten salt containing potassium ions for a third ion exchange to obtain composite strengthened glass.

[0007] In one embodiment, the first molten salt is a molten salt containing lithium nitrate, selected from lithium nitrate molten salt or a mixed molten salt of sodium nitrate with a lithium nitrate mass fraction ≥95 wt%; The second molten salt is a molten salt containing sodium nitrate, selected from sodium nitrate molten salt or potassium nitrate mixed molten salt with a sodium nitrate mass fraction ≥90 wt%; The third molten salt is a molten salt containing potassium nitrate, selected from potassium nitrate molten salt or a mixed molten salt of sodium nitrate with a potassium nitrate mass fraction ≥90 wt%.

[0008] In one embodiment, the temperature of the first ion exchange and the temperature of the second ion exchange are greater than or equal to the temperature of the third ion exchange.

[0009] In one embodiment, the temperature of the first ion exchange is 380°C-480°C, and the time of the first ion exchange is 0.5 hours-8 hours.

[0010] In one embodiment, the temperature of the second ion exchange is 400°C-480°C, and the time of the second ion exchange is 0.5 hours-6 hours.

[0011] In one embodiment, the temperature of the third ion exchange is 360°C-420°C, and the time of the third ion exchange is 0.5 hours-3 hours.

[0012] The present invention also provides a composite reinforced glass based on pre-lithiation and two-step ion exchange. The compressive stress inside the composite reinforced glass is distributed in a three-segment composite manner, consisting of an ultra-high stress surface layer, a stress transition zone, and a deep basic compressive stress zone from the surface to the interior.

[0013] The ultra-high stress surface layer is distributed within a range of 0~20μm from the surface of the composite reinforced glass, and the surface residual compressive stress CS≥400MPa. The stress transition zone is located below the ultra-high stress surface layer and extends to a depth of more than 50 μm below the surface of the composite reinforced glass. The residual compressive stress in the stress transition zone is ≥200 MPa. The deep foundation compressive stress zone is located below the stress transition zone, and the residual compressive stress decreases gradually with increasing depth.

[0014] The compressive stress layer depth of the composite strengthened glass is DOL≥80μm, and the central tensile stress CT of the composite strengthened glass is ≤70MPa.

[0015] Compared with the prior art, the present invention has the following beneficial effects: This invention provides a method for preparing composite strengthened glass based on pre-lithiation and two-step ion exchange. By innovatively combining the deep modification capability of lithium exchange with the high-strength building capability of potassium / sodium dual-strength exchange in both time and space, a synergistic strengthening effect greater than the sum of its parts (1+1>2) is achieved. The pre-lithiation process forms a deep, flexible modification foundation, upon which the subsequent potassium / sodium dual-strength exchange process constructs a high-strength surface structure. This synergistic mechanism gives the glass a unique "high surface peak-smooth deep base" composite stress structure. High surface compressive stress significantly improves the glass's hardness and scratch resistance, while the large compressive stress layer depth (DOL) and smooth stress gradient effectively inhibit the initiation and propagation of deep cracks, greatly enhancing the glass's impact resistance, drop resistance, and fatigue resistance. Simultaneously, the deep base compressive stress zone effectively anchors the central tensile stress. While achieving high surface compressive stress and a deep compressive stress layer, the central tensile stress (CT) is controlled at a low level, significantly reducing the risk of spontaneous breakage due to stress imbalance and improving the long-term reliability of the product. Furthermore, the key parameters of the three-step process of this invention, such as temperature, time, and molten salt composition, can be independently and precisely controlled, enabling customized stress curve design for different glass compositions and target performance requirements, thus possessing extremely strong process flexibility and operability. Attached Figure Description

[0016] Figure 1 This is a schematic diagram comparing the internal stress distribution curves of glass obtained by the traditional single-step potassium exchange process (Comparative Example 1) and the traditional two-stage strengthening process (Comparative Example 2) with the composite strengthening process implemented in this invention (Example 1). Figure 2This is a flowchart of the three-step chemical strengthening process of the present invention; Figure 3 The graph shows the effect of different pre-lithiation times (t1) on the final compressive stress layer depth (DOL) of the composite reinforced glass. Detailed Implementation

[0017] To enable those skilled in the art to understand the features and effects of the present invention, the terms and expressions used in the specification and claims are explained and defined in general below. Unless otherwise specified, all technical and scientific terms used herein have the ordinary meaning understood by those skilled in the art regarding the present invention, and in case of conflict, the definitions in this specification shall prevail.

[0018] The theories or mechanisms described and disclosed herein, whether right or wrong, should not in any way limit the scope of the invention, that is, the contents of the invention can be implemented without being limited by any particular theory or mechanism.

[0019] In this document, all features defined by numerical ranges or percentage ranges, such as numerical values, quantities, contents, and concentrations, are for the sake of brevity and convenience only. Accordingly, descriptions of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible sub-ranges and individual numerical values ​​(including integers and fractions) within those ranges.

[0020] In this article, unless otherwise specified, “contains,” “includes,” “containing,” “has,” or similar terms cover the meanings of “composed of” and “mainly composed of,” for example, “A contains a” covers the meanings of “A contains a and others” and “A contains only a.”

[0021] For the sake of brevity, not all possible combinations of the technical features in each implementation scheme or embodiment are described herein. Therefore, as long as there is no contradiction in the combination of these technical features, the technical features in each implementation scheme or embodiment can be combined arbitrarily, and all possible combinations should be considered within the scope of this specification.

[0022] This invention relates to the field of chemical strengthening technology for special glasses, specifically to a lithium aluminum silicate glass and its preparation method that optimizes the stress distribution on the glass surface through a composite ion exchange process to obtain ultra-high strength and high impact resistance.

[0023] like Figure 2 As shown, this invention provides a method for preparing composite strengthened glass based on pre-lithiation and two-step ion exchange, comprising the following steps: S1. Pre-lithiation ion exchange treatment: A lithium-sodium aluminum-silicon glass or sodium aluminum-silicon glass substrate (a sodium-containing silicate glass substrate) is immersed in a first molten salt containing lithium ions for the first ion exchange. The first molten salt is a molten salt containing lithium nitrate (LiNO3), the exchange temperature T1 is 380℃-480℃, and the exchange time t1 is 0.5 hours-8 hours. The pre-lithiation ion exchange treatment allows lithium ions (LiNO3) to undergo a first ion exchange. + It deeply penetrates the glass surface to adjust the distribution of alkali metal ions inside the glass and the glass ion packing density.

[0024] S2. First Step Ion (Sodium Ion) Exchange Treatment: The pre-lithiated glass treated in S1 is immersed in a second molten salt containing sodium and potassium ions for a second ion exchange. The second molten salt is a mixed molten salt containing sodium nitrate (NaNO3) and potassium nitrate (KNO3), wherein the mass fraction of NaNO3 is ≥90%, the exchange temperature T2 is 400℃-480℃, and the exchange time t2 is 0.5 hours-6 hours. This step allows sodium ions (NaNO3) to exchange through a process that allows sodium ions ... + ) and lithium ions (Li + The exchange occurs in the deep regions of the glass to form an intermediate glass with high stress depth and not low compressive stress.

[0025] S3. Second step: Stress adjustment and exchange treatment: The intermediate glass treated in S2 is immersed in a third molten salt containing potassium ions (a third molten salt containing sodium and potassium ions) for a third ion exchange. The third molten salt is a molten salt containing potassium nitrate (KNO3), wherein the mass fraction of KNO3 is ≥90%, and the balance is sodium nitrate. The exchange temperature T3 is 360℃-420℃, and T3≤T1, T3≤T2. The exchange time t3 is 0.5 hours-3 hours. This step is used to adjust the stress distribution, deepen the compressive stress layer, increase the surface compressive stress, and smooth the stress gradient to obtain the composite strengthened glass.

[0026] The silicate glass substrate is aluminosilicate glass, and its composition, by molar percentage, includes: SiO2: 50%–70%, Al2O3: 10%–25%, Na2O: 5%–16.5%, Li2O: 0%–10%, K2O: 0%–2%, MgO: 0%–5%, and ZrO2: 0%–5%.

[0027] Preferably, the silicate glass substrate is lithium sodium aluminum silicate glass, and its composition, by molar percentage, includes: SiO2: 50-70%, Al2O3: 10-25%, Na2O: 5-15%, Li2O: 0.1-5%, MgO: 0-5%, ZrO2: 0-5%, wherein the molar ratio of Al2O3 / Na2O is greater than or equal to 1.0.

[0028] In step S1, the first molten salt is pure LiNO3 molten salt, or a mixed molten salt of LiNO3 and NaNO3 with more than 95 wt% LiNO3.

[0029] The intermediate glass is further cleaned and dried between steps S1, S2 and S3.

[0030] Secondly, the present invention provides a composite reinforced glass prepared by the above-described preparation method.

[0031] The composite reinforced glass is characterized by having a non-monotonic (adjustable) composite compressive stress distribution curve inside, which includes the following components from the surface to the interior: Ultra-high stress surface layer region: formed by step S3, with surface compressive stress CS ≥ 400MPa within a range of 0-20μm from the surface; The stress transition zone is located below the ultra-high stress surface layer and extends to a depth of more than 50 μm below the surface of the composite reinforced glass. The residual compressive stress in the stress transition zone is ≥200 MPa.

[0032] The deep foundation compressive stress zone is located below the stress transition zone, and the residual compressive stress decreases gradually with increasing depth.

[0033] The compressive stress layer depth DOL of the composite reinforced glass (measured at zero compressive stress) is ≥ 80 μm.

[0034] The distance and slope of the line connecting the inflection point of the stress transition region to the origin (0,0) are adjustable.

[0035] The distance between the inflection point of the stress transition region and the line connecting the origin (0,0) is 130~210.

[0036] The slope of the line connecting the inflection point of the stress transition region to the origin (0,0) is 15.85~33.3MPa / um.

[0037] The stress distribution curve can be optimized using S1.

[0038] Preferably, the central tensile stress CT of the composite reinforced glass is ≤ 70 MPa, which comprehensively characterizes its strength and resistance to crack propagation.

[0039] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.

[0040] The following examples use instruments and equipment conventional in the art. Experimental methods in the following examples, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer. All raw materials used in the following examples are conventional commercially available products with specifications conventional in the art. In this specification and the following examples, unless otherwise specified, "%" refers to weight percentage, "parts" refers to parts by weight, and "ratio" refers to weight proportion.

[0041] Example 1 like Figure 2 As shown, this embodiment provides a method for preparing composite strengthened glass based on pre-lithiation and two-step ion exchange, including the following steps: Glass substrate provided: A commercial lithium sodium aluminum silicon glass is selected, with the following molar composition: SiO2 64%, Al2O3 16%, Na2O 12%, Li2O 2%, MgO 3%, ZrO 23%. Al2O3 / Na2O ≈ 1.33.

[0042] Pre-lithiation treatment (S1): Immerse the glass substrate in pure LiNO3 molten salt and exchange it at 450°C for 4 hours. After completion, remove it, clean and dry it.

[0043] Step 1 Sodium exchange (S2): Immerse the pre-lithiated glass in pure NaNO3 molten salt and exchange it at 420°C for 2 hours. Then remove it, clean it, and dry it.

[0044] The second step, stress conditioning (S3), involves immersing the glass from the previous step in a mixed molten salt of NaNO3:KNO3 = 10:90 (wt%) and exchanging it at 400°C for 0.5 hours. The glass is then removed, cleaned, and dried to obtain composite strengthened glass A.

[0045] Comparative Example 1 (Traditional Single-Step Potassium Exchange) The same glass substrate was directly immersed in pure KNO3 molten salt and exchanged at 400°C for 6 hours to obtain reinforced glass B.

[0046] Comparative Example 2 (Traditional Two-Strength Process) The same glass substrate was first immersed in pure NaNO3 molten salt (420℃, 6h), then cleaned and immersed in a mixed molten salt of NaNO3:KNO3 = 10:90 (wt%) (400℃, 1h) to obtain reinforced glass C.

[0047] Performance testing and characterization: The surface compressive stress (CS) and compressive stress layer depth (DOL) were measured using a surface stress meter (FSM-6000LE), and the complete stress profile was measured using a scattered light polarimeter (SCALP).

[0048] The results are shown in the table below:

[0049] Results analysis: like Figure 1 As shown, the stress curve of sample A in this invention is significantly different from that of the comparative example. It has the highest stress peak (CS=980 MPa) at the outermost layer, followed by a gradual decrease in stress, maintaining significant compressive stress in the deeper layers (>50 μm), and finally dropping to zero at approximately 110 μm. This unique "high and deep" stress structure results in its comprehensive performance indicators far exceeding those of the comparative example, with a comprehensive and significant improvement in four-point bending strength and resistance to falling ball impact.

[0050] Examples 2-4 The time t1 of the pre-lithiation step S1 was changed (to 1 h, 4 h, and 8 h respectively), while keeping the parameters of S2 and S3 the same as in Example 1.

[0051] The results are as follows Figure 3 As shown, with the increase of t1, the final glass density (DOL) increases significantly, while CS decreases slightly but remains at a high level. This indicates that by adjusting S1, the depth of the "base layer" can be effectively controlled, achieving customized performance.

[0052] This invention is not limited to the specific embodiments described above. Those skilled in the art can make various modifications and improvements within the inventive concept and scope defined in the specification. For example, adjusting the temperature, time, and molten salt ratio in each step; adding a small amount of auxiliary salts (such as sulfates or carbonates) to the molten salt to improve the exchange effect, etc., all fall within the protection scope of this invention.

[0053] This invention discloses a composite strengthened glass based on a two-step ion exchange (three-step chemical strengthening) process using pre-lithiation and its preparation method, belonging to the field of chemical strengthening of special glasses. The method first involves fusing sodium-aluminum-silicon glass in Li... + High-temperature pre-lithiation treatment is performed in molten salt to form a deeply modified base layer; followed by a two-step ion exchange: first in Na... + / K + A high surface compressive stress layer is formed in the mixed molten salt, and then in Na + / K + Stress gradients are adjusted and smoothed in a mixed molten salt. This composite process synergistically utilizes Li + The rapid deep diffusion characteristics and K + / Na +The high-stress construction capability of the exchange process results in glass with a unique composite compressive stress structure of "high surface stress peak - deep and gentle stress base zone". This glass simultaneously possesses high surface compressive stress (≥800 MPa), large compressive stress layer depth (≥80 μm), gentle stress gradient, and low central tensile stress (≤70 MPa), resulting in a comprehensive and significant improvement in its bending strength, impact resistance, and fatigue resistance. It is particularly suitable for fields such as electronic cover glass where extremely high strength and reliability are required.

[0054] The above content is only for illustrating the technical concept of the present invention and should not be construed as limiting the scope of protection of the present invention. Any modifications made to the technical solution based on the technical concept proposed in this invention shall fall within the scope of protection of this invention.

Claims

1. A method for preparing composite strengthened glass based on pre-lithiation and two-step ion exchange, characterized in that, Includes the following steps: Pre-lithiated glass is prepared by immersing a lithium sodium aluminum silicon glass substrate or a sodium aluminum silicon glass substrate in a first molten salt containing lithium ions for the first ion exchange. Pre-lithiated glass is immersed in a second molten salt containing sodium ions for a second ion exchange to obtain intermediate glass; The intermediate glass is immersed in a third molten salt containing potassium ions for a third ion exchange to obtain composite strengthened glass.

2. The method for preparing composite strengthened glass based on pre-lithiation and two-step ion exchange according to claim 1, characterized in that, The first molten salt is a molten salt containing lithium nitrate, selected from lithium nitrate molten salt or a mixed molten salt of sodium nitrate with a lithium nitrate mass fraction greater than or equal to 95 wt%; The second molten salt is a molten salt containing sodium nitrate, selected from sodium nitrate molten salt or potassium nitrate mixed molten salt with a sodium nitrate mass fraction ≥90 wt%; The third molten salt is a molten salt containing potassium nitrate, selected from potassium nitrate molten salt or a mixed molten salt of sodium nitrate with a potassium nitrate mass fraction ≥90 wt%.

3. The method for preparing composite strengthened glass based on pre-lithiation and two-step ion exchange according to claim 1, characterized in that, The temperatures of the first and second ion exchanges are greater than or equal to the temperature of the third ion exchange.

4. The method for preparing composite strengthened glass based on pre-lithiation and two-step ion exchange according to claim 1, characterized in that, The temperature of the first ion exchange is 380℃-480℃, and the time of the first ion exchange is 0.5 hours-8 hours.

5. The method for preparing composite strengthened glass based on pre-lithiation and two-step ion exchange according to claim 1, characterized in that, The temperature of the second ion exchange is 400℃-480℃, and the time of the second ion exchange is 0.5 hours-6 hours.

6. The method for preparing composite strengthened glass based on pre-lithiation and two-step ion exchange according to claim 1, characterized in that, The temperature of the third ion exchange is 360℃-420℃, and the time of the third ion exchange is 0.5 hours-3 hours.

7. A composite strengthened glass based on pre-lithiation and two-step ion exchange, characterized in that, The composite strengthened glass based on pre-lithiation and two-step ion exchange, as described in any one of claims 1 to 6, is prepared by a method that provides a composite strengthened glass in which the compressive stress inside the composite strengthened glass is distributed in a three-segment composite manner, consisting of an ultra-high stress surface layer, a stress transition zone, and a deep basic compressive stress zone from the surface layer to the interior.

8. A composite strengthened glass based on pre-lithiation and two-step ion exchange according to claim 7, characterized in that, The ultra-high stress surface layer is distributed within a range of 0~20μm from the surface of the composite strengthened glass, and the surface residual compressive stress CS≥400MPa; The stress transition zone is located below the ultra-high stress surface layer and extends to a depth of more than 50 μm below the surface of the composite reinforced glass. The residual compressive stress in the stress transition zone is ≥200 MPa. The deep foundation compressive stress zone is located below the stress transition zone, and the residual compressive stress decreases gradually with increasing depth.

9. A composite strengthened glass based on pre-lithiation and two-step ion exchange according to claim 7, characterized in that, The compressive stress layer depth of the composite reinforced glass is DOL≥80μm.

10. A composite strengthened glass based on pre-lithiation and two-step ion exchange according to claim 7, characterized in that, The central tensile stress CT of the composite reinforced glass is ≤70MPa.